Evaluation of Thermal Processing of Commercially Available Milk Brands in Lahore - Ayesha,; Fatima, Raiha; Hussain, Saddam; Sajid, Ali Hamza; Murshid, Misbah; Iqbal, Muhammad Javid (Journal of Basic and Emerging Sciences, 2024)
Raw milk and commercially available milk samples were tested for the alkaline phosphatase activity to evaluate the efficacy of the pasteurization of milk. A colorimetric assay used for the kinetic determination of serum alkaline phosphatase to detect ALP in the targeted samples. The colorimetric assay uses p-nitrophenyl phosphate as the reaction substrate. When ALP acts upon this substrate, it breaks down into a phosphate group and p-nitrophenol which produces the characteristic yellow colour in the solution. The increase in absorbance of the solution measured at 405 nm is directly related to the ALP activity in the respective sample. Three raw milk samples were tested firstly as a whole and then after fat removal through centrifugation at 4000 rpm for 30 min. Seven UHT and three naturally pasteurized commercial milk samples available in the local market were used for the ALP detection in this study. Significant values for ALP activity in raw milk samples was observed whereas, for all the pasteurized samples, the test was observed to be negative that indicate the effective pasteurization process before the milk was packed for marketing. Casein was the major protein found in milk as 3.43g per 100 ml of milk sample, whereas the values for standard deviation and relative standard deviation were 0.08 and 2.54 respectively. Based on the negative results for ALP and actual yield of casein found to be closer to the theoretical yield for all the samples it can be suggested that all the targeted milk brands were safe to be consumed.